Systematic Review : The Effect of Intervention Rehabilitation â€œComputer-Based Cognitive Training Programâ€ to Improve Cognitive Skills of Children with ADHD - Fitrianti Mahardika; Esti Yunitasari; Praba Rachmawati (Journal of Ners and Midwifery, 2021)
Attention Deficit Hyperactivity Disorder (ADHD) is a medical condition characterized by an inability to concentrate, hyperactivity, and impulsiveness. Children with ADHD tend to be careless, irritable, difficult to gather, difficult to carry out orders so it is important to treat this condition as early as possible. The purpose of this study was to analyze studies according to computer program-based cognitive rehabilitation interventions to improve the cognitive abilities of children with ADHD on empirical studies in the last five years. Journals or articles were obtained by searching in databases indexed by Scopus, PubMed, Science Direct, Garuda Portal using adequate keywords. The quality assessment of the study used inclusion and exclusion criteria. The framework used to conduct the review was PICOS and the inclusion criteria used English and Indonesian journals from 2015 to 2020. The data analysis and tabulation were carried out in articles or journals. Title, abstract, full text, and methodology were assessed to determine the eligibility of the article or journal. Researchers found 15 journals that match the inclusion and exclusion criteria, and passed the study selection and quality assessment. 7 journals discuss about training-based intervention programs and 8 journals discussed the game or game-based intervention programs. The 15 journals obtained came from four continents, Asia, America, Australia, and Europe. Computer-based intervention significantly improved the cognitive abilities of children with ADHD such as concentration skills, working memory, and academic learning outcomes. Modifications need to be made, among others, to facilitate parents who can not afford compatible facilities and infrastructure. In Indonesia, the modifications that are possibly made are the daily training program compared to video games.